Programming Scala tackle multicore complexity on the JVM - Subramaniam, Venkat (Pragmatic Bookshelf, 2009)
Describes how to use Scala to create applications for the Java VM.
Keywords: Scala (Computer program language); Java virtual machine; Java (Computer program language); Scala -- Programmiersprache